1992
DOI: 10.1038/bjc.1992.173
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity on chromosomes 1 and 11 in carcinoma of the pancreas

Abstract: Summary Little is known of the molecular-genetic changes in carcinoma of the pancreas (CaP). In order to investigate the allele loss, or loss of heterozygosity (LOH), in CaP, we studied 13 patients with exocrine CaP and two with endocrine CaP using restriction fragment length polymorphism analysis. Twenty probes assigned to chromosomes 1, 5, 7, 9, 11, 12, 13, 14, 16, 17 and 18 were used. The frequency of LOH, or fractional allele loss (FAL), was found in two endocrine tumours to be 0.333 and 0.455 respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 29 publications
3
12
0
1
Order By: Relevance
“…For colorectal carcinomas, patients with a higher frequency of allelic losses had a considerably worse prognosis than did the other patients (Vogelstein et al, 1989). A similar correlation was observed in carcinomas of the pancreas (Ding et al, 1992). Thus this study showing a much lower frequency of allele loss in FLC than in HCC is in agreement with the above observations since FLC has a much better prognosis than HCC (Craig et at., 1980).…”
Section: Discussionsupporting
confidence: 81%
“…For colorectal carcinomas, patients with a higher frequency of allelic losses had a considerably worse prognosis than did the other patients (Vogelstein et al, 1989). A similar correlation was observed in carcinomas of the pancreas (Ding et al, 1992). Thus this study showing a much lower frequency of allele loss in FLC than in HCC is in agreement with the above observations since FLC has a much better prognosis than HCC (Craig et at., 1980).…”
Section: Discussionsupporting
confidence: 81%
“…A search of UniGene disclosed that these ESTs were located in UniGene cluster Hs.157119T, which was assigned to chromosome 1. This chromosomal assignment was supported by FISH analysis, which mapped SMRZ to chromosome 1p33-34, a region associated with cell proliferation and differentiation (45)(46)(47)(48)(49)(50)(51)(52)(53)(54). This predicted putative role of SMRZ based on the chromosomal assignment was supported by the subcellular localization experiment, which showed that SMRZ is located in the nucleus using C2C12 myoblasts transfected with SMRZ.…”
Section: Discussionsupporting
confidence: 52%
“…Gain of chromosomes 20 and 7 and loss of 18 and Y are among the most common numerical changes also in colorectal adenocarcinomas (Muleris et al, 1990;Bardi et al, 1993), underscoring the karyotypic similarities among the various gastrointestinal cancers. Genetic similarities are evident also at the molecular level, with loss of heterozygosity on Ip, 5q, 1 lq, 17p and 18q being detected not only in colorectal but also in pancreatic adenocarcinomas (Neuman et al, 1991;Ding et al, 1992;Hohne et al, 1992).…”
Section: Discussionmentioning
confidence: 99%